Chlorpyrifos induces genotoxic effects in human leukocytes in vitro at low concentrations - Elvio Adílio Serpa; Elisandra Gomes Schmitt; Luísa Zuravski; Michel Mansur Machado; Luís Flávio Souza de Oliveira (Universidade Estadual de Maringá, 2019)
Chlorpyrifos (CPF) is an organophosphate widely marketed as a pesticide. However, only few studies have investigated its genotoxic potential, especially in human tissues or cells, or the minimal concentration capable of inducing damage. This study analyzed the in vitro genotoxic potential of CPF in cultured human leukocytes at concentrations of 3, 35, and 350 μg mL-1. Results demonstrated that the two highest concentrations exhibited an increase (~2-fold) in the micronucleus frequency (p < 0.01), the number of numerical chromosomal instabilities (~10-12 times, p < 0.05), and the number of apoptotic cells (~10- to 20-fold, p < 0.001). These results demonstrate the genotoxic potential of CPF and could open new discussions regarding its safety and toxicology.